Implementing Animated Disaster Mitigation Media Animation Video to Enhance Flood Preparedness Among Student At SDN Kali Baru 3 Bekasi - Devi Yulianti (STIKes RSPAD RSPAD Gatot Soebroto, 2024)
Background: Flooding is a persistent seasonal challenge in Indonesia, and young school-aged children represent one of the most vulnerable demographic groups during emergencies. Improving disaster response capability from an early age requires innovative educational approaches that capture children's interest. Objective: This study evaluated the effect of using animated cartoon videos as an educational modality to enhance flood disaster preparedness knowledge among elementary school children. Method: A quantitative research design using a quasi-experimental approach with a one-group pretest-posttest framework was implemented. The study involved 62 fourth-grade students aged 9–10 years at SDN Kali Baru 3 Bekasi, selected via total sampling. Knowledge levels were evaluated using a verified questionnaire before and after the intervention. The data were processed using univariate analysis and the non-parametric Wilcoxon signed-ranks test because of non-normal data distribution. Results: Prior to the educational intervention, 3.2% of the participants had poor knowledge, 37.1% had sufficient knowledge, and 59.7% possessed good knowledge. Following the screening of the animated cartoon videos, 100% of the participants achieved the